2006
DOI: 10.1016/j.virol.2006.06.026
|View full text |Cite
|
Sign up to set email alerts
|

The human severe acute respiratory syndrome coronavirus (SARS-CoV) 8b protein is distinct from its counterpart in animal SARS-CoV and down-regulates the expression of the envelope protein in infected cells

Abstract: The severe acute respiratory syndrome coronavirus (SARS-CoV), isolated from humans infected during the peak of epidemic, encodes two accessory proteins termed as 8a and 8b. Interestingly, the SARS-CoV isolated from animals contains an extra 29-nucleotide in this region such that these proteins are fused to become a single protein, 8ab. Here, we compared the cellular properties of the 8a, 8b and 8ab proteins by examining their cellular localizations and their abilities to interact with other SARS-CoV proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 35 publications
5
85
2
Order By: Relevance
“…Although SARS-CoV 8b gene product could be expressed in vivo when cloned directly behind a promoter [11][12][13]; the expression of 8a and 8b in SARS-CoVinfected cells is still controversial [9,10,13]. As shown above, we were unable to detect the protein expression of sgRNA 8 with the 5 0 viral leader sequence, which corroborated with a recent report on ORF8 expression [13].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although SARS-CoV 8b gene product could be expressed in vivo when cloned directly behind a promoter [11][12][13]; the expression of 8a and 8b in SARS-CoVinfected cells is still controversial [9,10,13]. As shown above, we were unable to detect the protein expression of sgRNA 8 with the 5 0 viral leader sequence, which corroborated with a recent report on ORF8 expression [13].…”
Section: Resultssupporting
confidence: 91%
“…Ten sgRNAs have been identified [5] and the SARS-CoV accessory proteins 3a, 3b, 6,7a, and 7b can be detected in infected cells or SARS patients besides structural proteins [7,8], while the expression of 8a and 8b is controversial [9][10][11][12][13]. Elucidation of the regulatory mechanism in the translation is important for understanding the pathogenesis of SARS-CoV; however, it is hard to compare the differential translation of sgRNAs because the steady-state level of viral proteins in infected cells reflects the sum of transcription, translation, and the relative stabilities of these transcriptional and translational products.…”
Section: Resultsmentioning
confidence: 99%
“…ORF8b encodes an 84-aa polypeptide and residues 9-84 are identical to the C-terminal of 8ab (Oostra et al, 2007). Whereas Keng et al have demonstrated by indirect immunofluorescence that 8a and 8b are expressed in SARS-CoVinfected Vero E6 cells, Oostra et al were unable to detect 8b in SARS-CoV-infected Vero E6 cells (Oostra et al, 2007;Keng et al, 2006). Although there is no data regarding the expression of 8a or 8b in vivo, Chen et al have identified anti-p8a antibodies in two out of 37 patients with SARS (Chen et al, 2007).…”
Section: Sars-cov P7bmentioning
confidence: 99%
“…Not only do in vitro and in vivo studies show that ORF8ab is ubiquitinated, but both ORF8a and ORF8b also binds to monoubiquitin and polyubiquitin, suggesting the potential involvement of these proteins in the pathogenesis of SARS-CoV [116]. ORF8ab interacts with SARS-CoV proteins S, M, ORF3a and ORF7a [118], all of which have been shown to be structural proteins. …”
Section: Sars Accessory Proteinsmentioning
confidence: 99%
“…ORF8b down-regulates the expression of SARS-CoV E, a process that could be inhibited by the addition of proteasome inhibitors [116]. For this reason, E is not detectable in SARS-CoV-infected cells that are expressing high levels of ORF8b [118]. Similarly to ORF6, overexpression of ORF8b in mammalian cells also induces DNA synthesis.…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%